Watering the Grassroots: A Strategy for Social Movement Support - Joyce, Mary (Transparency & Accountability Initiative, 2015)
In this third and final think piece exploring the role of grassroots o rganizations and movements for state accountability (find the previous pieces here and here), the author Mary Joyce, proposes new thinking a bout how funders and other external organizations can best support soc ial movements. Funding and other support for popular organizations and movements is not straightforward, and there are potential risks and d istortions involved. Interested supporters need to clearly identify an d articulate these obstacles in their discussions with movement activi sts before pursuing and funding or other support activities. This thin k piece outlines several potential avenues of support: small, flexible grants; funding intermediary organizations; providing external consul tants or researchers to work with movements; and other options as well . These suggestions provide ideas for funders and other organizations seeking to move beyond projects to supporting robust accountability ec osystems, in which grassroots organizations and movements play a criti cal role.